Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/(sici)1521-3803(20000101)44:1<7::aid-food7>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and characterization ofBalanites aegyptiacaDel. kernel proteins. Effect of defatting, air classification, wet sieving and aqueous ethanol treatment on solubility, digestibility, amino acid composition and sapogenin content

Abstract: In order to find alternative protein sources in African regions where protein deficiency in nutrition is prevailing, solubility, in-vitro digestibility, amino acid composition and chemical score of Balanites aegyptiaca Del. kernel proteins were investigated as a function of different processing steps including defatting, air classification, wet sieving and aqueous ethanol treatment. Air classification delivered a fine fraction of 58.1% of the total protein. Applying a wet sieving process, a protein concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Since saponins show anti-hypercholesteremic, hypoglycemic and anti-carcinogenic action (Pettit et al, 1991;Oakenfull and Sidhu, 1990;Abdel-Rahim et al, 1986;Sidhu and Oakenfull 1986), great attention has been paid to saponin-containing plants in order to recover saponins as additives for food products, as pharmaceuticals and as chemical ingredients (Mohamed et al, 2000). Chapagain and Wiesman (2007) chromatographically separated nine compounds and determined their masses in the negative ion mode; subsequent fragmentation of each component was then carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Since saponins show anti-hypercholesteremic, hypoglycemic and anti-carcinogenic action (Pettit et al, 1991;Oakenfull and Sidhu, 1990;Abdel-Rahim et al, 1986;Sidhu and Oakenfull 1986), great attention has been paid to saponin-containing plants in order to recover saponins as additives for food products, as pharmaceuticals and as chemical ingredients (Mohamed et al, 2000). Chapagain and Wiesman (2007) chromatographically separated nine compounds and determined their masses in the negative ion mode; subsequent fragmentation of each component was then carried out.…”
Section: Introductionmentioning
confidence: 99%
“…B. aegyptiaca is the tree whose all organs are used either for food, medicinal purposes or for works services. Various parts of the tree have been used in folk medicine in many parts of Africa and Asia (Kipkore et al, 2014;Mohamed et al, 2002Mohamed et al, , 2000. Anti-appetant, anti-diabetic, molluscicidal, anthelmintic and contraceptive activities have been revealed in various Balanites extracts (Kamel et al, 1991;Liu & Nakanis, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Malki et al [8] have reported antioxidant potential of Balanites aegyptiaca (L) Del in combating disease. Studies have also reported that Balanites aegyptiaca (L) Del (L) Del have been used as folk medicine in many regions of Africa and Asia [1,9,10]. Literature have reported antifeedant, molluscicide, anthelminthic, and contraceptive activities of Balanites aegyptiaca (L) Del extracts [11,12].…”
Section: Introductionmentioning
confidence: 99%